Examination of a foot mounted IMU-based methodology for a running gait assessment - Young, Fraser; Mason, Rachel; Wall, Conor; Morris, Rosie; Stuart, Samuel; Godfrey, Alan (Frontiers in Sports and Active Living, 2022)
Gait assessment is essential to understand injury prevention mechanisms during running where high impact-forces can lead to a range of injuries in the lower extremities. Selection of the correct running shoe can minimize risk of injury through matching a runner’s gait to a particular set of cushioning technologies found in modern shoes (neutral/support cushioning). Selection of the correct running shoe requires understanding of a runner’s biomechanics such as determining foot orientation when it strikes the ground. Previous work involved a low-cost approach with a foot mounted inertial measurement unit (IMU) and associated zero-crossing (ZC) based methodology to objectively understand a runner’s biomechanics (in any setting) to inform shoe selection. Here, an investigation of the previously presented ZC-based methodology is presented to determine its validity for running gait assessment to inform shoe selection in a range of running abilities from novice (8km/h) to experienced (16km/h+). In comparison to Vicon 3D motion tracking data, the presented approach can extract pronation, foot strike location and ground contact time with good (ICC(2,1) > 0.750) to excellent (ICC(2,1) > 0.900) agreement between 8-12km/h runs. However, at higher speeds (14km/h+) the ZC-based approach begins to deteriorate in performance, suggesting other features and approaches may be more suitable for faster running and sprinting tasks.